Entre batismos, testamentos e cartas: as alforrias e as dinâmicas de mestiçagens em São João del-Rei (c.1750 c.1850) - Cristiano Lima da Silva (2017)
This thesis studies the manumissions registered in baptism books, wills and notaries note books of São João del-Rei, Minas Gerais, in the period between c.1750 to c.1870, in the Church of Our Lady of Pilar in São João del-Rei, Minas Gerais and at the Historical Archive of IPHAN. From the information collected in these sources, we identified quantitatively and qualitatively the profile of masters and freedmen, the modalities, the varied motivations, interests and conditions required, so that men, women and children originating from Africa, and their descendants born in Brazil, were able to reach freedom. Based on the theoretical framework of the Social History of Culture, the results of this research point to the asymmetric relations established between owners and their captives, guided by distinctions, ratings and social hierarchies, dynamics of miscegenation (biological and cultural) and social mobility, often associated to financial and moral agreements, moral bonding and/or of solidarity which, in different ways, marked the complex process of granting/conquering manumissions.